2016
DOI: 10.1016/j.neuron.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Distributed and Mixed Information in Monosynaptic Inputs to Dopamine Neurons

Abstract: SUMMARY Dopamine neurons encode the difference between actual and predicted reward, or reward prediction error (RPE). Although many models have been proposed to account for this computation, it has been difficult to test these models experimentally. Here we established an awake electrophysiological recording system, combined with rabies virus and optogenetic cell-type identification, to characterize the firing patterns of monosynaptic inputs to dopamine neurons while mice performed classical conditioning tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
242
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(268 citation statements)
references
References 90 publications
25
242
1
Order By: Relevance
“…These types generally showed significantly different firing rates, except that the difference between type-1 and type-3 MSt neurons (excitation subtype) were not statistically different. It is thus suggested the recorded set of neurons formed a continuum spectrum, rather than distinct groups separated by gaps, similarly to those shown in recent comparable study in mice (Tian et al, 2016). …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These types generally showed significantly different firing rates, except that the difference between type-1 and type-3 MSt neurons (excitation subtype) were not statistically different. It is thus suggested the recorded set of neurons formed a continuum spectrum, rather than distinct groups separated by gaps, similarly to those shown in recent comparable study in mice (Tian et al, 2016). …”
Section: Resultssupporting
confidence: 81%
“…In a very recent paper in mice Tian et al (2016), that appeared after the submission of our present study), neuronal activities were recorded from neurons with confirmed monosynaptic connection to DA-ergic neurons. These input neurons were distributed widely in various brain regions including dorsal and ventral striatum, as well as lateral hypothalamus and tegmental nuclei.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, orbital frontal cortex (OFC) provides VTA with information about complex aspects of the task that must be inferred to predict the future value of rewards [44], and the ventral striatum contributes learning about the duration of task states [45]. Contrary to recent suggestions [46],this shows that VTA neurons do receive qualitatively different types of associative information from multiple sources. Understanding how dopaminergic (and other) neurons in the VTA integrate input from the LH GABA neurons and these other sources, and return it to update these various representations, is an important future goal.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the existing data on plasticity in the VTA is focused on excitatory input onto DA neurons, with good reason. DA neurons can switch from tonic firing activity (1-4 Hz) to a burst firing pattern (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at the presentation of behaviourally relevant stimuli (Paladini & Roeper, 2014), and this switch appears to be triggered by presynaptic excitatory inputs (Chergui et al, 1993;Floresco et al, 2003) arising from various parts of the brain (Watabe-Uchida et al, 2012;Beier et al, 2015;Tian et al, 2016). Thus, excitatory inputs critically influence DA neuron output, and consequently, DA-dependent behaviours.…”
Section: Excitatory Synapse Plasticitymentioning
confidence: 99%